Issues in the estimation of dynamic happiness models: A Comment on "Does childhood predict adult life satisfaction?" - Alan T. Piper; Geoffrey T. Pugh (Kiel Institute for the World Economy (IfW), 2015)
This short note offers methodological comments on an 'Economic Journal' article (Frijters, P., Johnston, D.W. and Shields, M.A. (2014). Does Childhood Predict Adult Life Satisfaction? Evidence from British Cohort Surveys. 'Economic Journal' 124(580): F688-F719). The comments consider its use of a dynamic model - the inclusion of a lagged dependent variable - and its employment of General Method of Moments (GMM) estimation.
Keywords: I31; 330; Life Satisfaction; dynamic panel analysis; GMM